Leighton and hille-type oscillation criteria for second order damped elliptic equations - Xu, Zhiting (Utilitas Mathematica, 2008)
Leighton and Hille-type oscillation criteria are established for the second order damped elliptic differential equation (Equation Presented) The obtained results extend and improve some known results in literature.